2021
DOI: 10.3389/fmed.2021.797428
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Thickness Profile in Chorioretinal Diseases: Beyond the Macula

Abstract: Enhanced depth imaging optical coherence tomography (EDI-OCT) and swept-source OCT (SS-OCT) have emerged as essential diagnostic tools in the study and management of various chorioretinal diseases. Evidence from early clinical studies using EDI-OCT and SS-OCT indicates that choroidal dysfunction plays a major role in the pathogenesis of chorioretinal diseases. Measurement of choroidal thickness (CT) has already become a major research and clinical method, and CT is considered as an indicator of choroidal statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 151 publications
0
12
0
Order By: Relevance
“…Automated solutions have been suggested to lessen the inaccuracy of subjective disparities present in the procedures [40,41]. The importance of measurement of ChT has been emphasized in the study of chorioretinal diseases, where choroidal dysfunction plays an important role in their pathogenesis, namely central serous retinopathy, polypoidal choroidal vasculopathy, age-related macular degeneration, retinal vascular diseases, retinitis pigmentosa, glaucoma, and uveitis [42][43][44]. The advent of OCT has provided us with a tool to directly image and measure the ChT and volume to better understand pathogenic mechanisms of ocular and metabolic, inflammatory, neurodegenerative, and metabolic systemic diseases affecting the choroid [44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…Automated solutions have been suggested to lessen the inaccuracy of subjective disparities present in the procedures [40,41]. The importance of measurement of ChT has been emphasized in the study of chorioretinal diseases, where choroidal dysfunction plays an important role in their pathogenesis, namely central serous retinopathy, polypoidal choroidal vasculopathy, age-related macular degeneration, retinal vascular diseases, retinitis pigmentosa, glaucoma, and uveitis [42][43][44]. The advent of OCT has provided us with a tool to directly image and measure the ChT and volume to better understand pathogenic mechanisms of ocular and metabolic, inflammatory, neurodegenerative, and metabolic systemic diseases affecting the choroid [44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, SS-OCT reduces motion artifacts and permits high-speed, high-resolution imaging and better visualization of the ONH. (23,24,41) In addition, SS-OCT showed excellent repeatability and reproducibility in ONH parameters. (42) Therefore, the current study used SS-OCT to analyze ONH characteristics in myopic anisometropia.…”
Section: Discussionmentioning
confidence: 87%
“…The choroid is one of the most vascularized structures in the human body, supplying most of the blood, nutrients, and oxygen to the retina. (14,24,51) More evidence has shown two other functions of the choroid: adjusting the position of the retina by changing the CT and releasing growth factors to regulate the modulation of vascularization and scleral remodeling, as well as promoting ocular growth. (52,53) Variations in CT may be predominantly driven by changes in choroidal blood ow, given that the choroid is essentially a vascular structure capable of quickly altering blood ow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10] In fact, these breakthroughs have augmented our insight of choroidal changes in various systemic diseases especially those related with a disrupt vascular state. [11] Loureiro et.al found that choroidal thickness (CT) in temporal and inferotemporal sectors were signi cantly lower in MetS patients. [12] Factors pertinent to NAFLD including obesity, [13,14] cardiovascular risk factors [15] and insulin resistance [16] have also proven to be negatively correlated with CT.…”
Section: Introductionmentioning
confidence: 99%